Pengaruh Kondisi Sosial Ekonomi Keluarga Terhadap Prestasi Belajar Mahasiswa FISIP Universitas Teknologi Sumbawa - Firmandika Firmandika; Indah Fitriana Sari (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The aim of this research is to determine the influence of family socio-economic conditions on the learning achievement of Sumbawa University of Technology FISIP students. The research was conducted at Sumbawa University of Technology with the research population being all students from the Faculty of Social and Political Sciences (FISIP), totaling 481 students. From this population, a sample of 83 students was taken which was obtained from the Slovin formula using a simple random sampling technique. This research uses quantitative methods. Research data was obtained through a research instrument in the form of a questionnaire with a Likert scale, then processed and analyzed using simple linear regression analysis techniques. The results of this research show that family socio-economic conditions have a significant effect on the learning achievement of FISIP students at Sumbawa University of Technology.